Getting back into the labor market: the effects of start-up subsidies for unemployed females - Caliendo, Marco; Künn, Steffen (Berlin, 2012)
"A shortage of skilled labor and low female labor market participation are problems many developed countries have to face. Beside activating inactive women, one possible solution is to support the re-integration of unemployed women. Due to female-specific labor market constraints (preferences for exible working hours, discrimination), this is a difficult task, and the question arises whether active labor market policies (ALMP) are an appropriate tool to do so. Promoting self-employment among the unemployed might be promising. Starting their own business might give women more independence and exibility in allocating their time to work and family. Access to long-term informative data allows us to close existing research gaps, and we investigate the impact of two start-up programs on long-run labor market and fertility outcomes of female participants. We find that start-up programs persistently integrate former unemployed women into the labor market and partly improve their income situations. The impact on fertility is less detrimental than for traditional ALMP programs."